Neoadjuvant Chemotherapy With Cisplatin and Gemcitabine Followed by Chemoradiation Versus Chemoradiation for Locally Advanced Cervical Cancer: A Randomized Phase II Trial - da Costa, Samantha Cabral S.; Bonadio, Renata Colombo; Gabrielli, Flavia Carolina G.; Aranha, Andrea S.; Dias Genta, Maria Luiza N.; Miranda, Vanessa C.; de Freitas, Daniela; Abdo Filho, Elias; Ferreira, Patrícia A.O.; Machado, Karime K.; Scaranti, Mariana; Carvalho, Heloísa de A.; et al. (Journal of clinical oncology, 2019)
Although chemoradiation therapy (CRT) with cisplatin remains the standard treatment of patients with locally advanced cervical cancer (LACC), 40% of patients present with disease recurrence. Additional treatment strategies are required to improve outcomes. We conducted a trial to evaluate the efficacy and safety of neoadjuvant chemotherapy (NAC) with cisplatin and gemcitabine followed by CRT. In this phase II trial, patients with LACC (International Federation of Gynecology and Obstetrics stage IIB to IVA or with positive lymph nodes) were randomly assigned to three cycles of NAC with cisplatin and gemcitabine followed by standard CRT with weekly cisplatin plus pelvic radiotherapy or to standard CRT alone. The primary end point was 3-year progression-free survival (PFS). Secondary end points were response rate, 3-year locoregional control, 3-year overall survival (OS), safety, and quality of life. From 107 patients enrolled in the trial, 55 were randomly assigned to the NAC arm and 52 to the CRT-alone arm. The majority of patients had squamous cell carcinoma (87.8%). After a median follow-up of 31.7 months, NAC was associated with an inferior PFS, with 3-year PFS rates of 40.9% 60.4% in the CRT arm (hazard ratio, 1.84; 95% CI, 1.04 to 3.26; = .033). NAC also was associated with a lower OS (3-year OS rate, 60.7% 86.8%; hazard ratio, 2.79; 95% CI, 1.29 to 6.01; = .006). After treatment completion, complete response rates were 56.3% in the NAC arm and 80.3% in the CRT arm ( = .008). Toxicities were similar in both arms, with the exception of hypomagnesemia and neuropathy being more common with NAC. This study shows that the addition of NAC consisting of cisplatin and gemcitabine to standard CRT is not superior and is possibly inferior to CRT alone for the treatment of LACC.